FAO technical guidelines for responsible fisheries N2: Precautionary approach to capture fisheries and species introductions - FAO (FAO, 1996)
The book contains detailed guidelines on how to conduct fishery management and research and how to develop and tranfer fishery technology in a context of uncertainly and responsible fisheries. Guidelines are also provided on species introduction, voluntary or accidental ( including through ballast water and sediment discharge ), recognizing the difficulty of ensuring a precautionary approach in relation to that issues. The guidelines are aimed at the governments, fisheries authorities, fishery industry, regional fishery management bodies.